2006
DOI: 10.1007/s10286-006-0330-y
|View full text |Cite
|
Sign up to set email alerts
|

Phase of the menstrual cycle does not affect orthostatic tolerance in healthy women

Abstract: Women of child-bearing age have a lower orthostatic tolerance (OT) than older women or men, and women suffering from frequent syncopal episodes often comment that their symptoms occur at certain times of the menstrual cycle. However, it is not known whether, in asymptomatic women, OT varies at different phases of the menstrual cycle. We studied 8 healthy asymptomatic women aged 26.8 +/- 3.4 years. We determined OT using a test of combined head-up tilting and lower body suction. We continuously monitored beat-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 42 publications
2
27
0
1
Order By: Relevance
“…Fu et al (8) reported that 5 of 11 women experienced presyncope during the EF phase, whereas only 3 experienced presyncope during the ML phase. Three recent studies indicate no differences in orthostatic tolerance during high and low hormone phases of the menstrual cycle, but these studies did not assess sympathetic baroreflex sensitivity (2,4,17). Instead, cardiovagal baroreflex sensitivity was assessed and determined to be similar during the various phases of the menstrual cycle (2,4,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fu et al (8) reported that 5 of 11 women experienced presyncope during the EF phase, whereas only 3 experienced presyncope during the ML phase. Three recent studies indicate no differences in orthostatic tolerance during high and low hormone phases of the menstrual cycle, but these studies did not assess sympathetic baroreflex sensitivity (2,4,17). Instead, cardiovagal baroreflex sensitivity was assessed and determined to be similar during the various phases of the menstrual cycle (2,4,17).…”
Section: Discussionmentioning
confidence: 99%
“…Three recent studies indicate no differences in orthostatic tolerance during high and low hormone phases of the menstrual cycle, but these studies did not assess sympathetic baroreflex sensitivity (2,4,17). Instead, cardiovagal baroreflex sensitivity was assessed and determined to be similar during the various phases of the menstrual cycle (2,4,17). The influence of menstrual phase on sympathetic baroreflex sensitivities during a maximal orthostatic stress test remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The type of contraceptives was not registered. Cardiovascular responses to LBNP seems to be unaffected by menstrual phase (5,16), and, furthermore, venous compliance and capacitance do not change over the course of the menstrual cycle or with oral contraceptive use (36). Some data from the young women and men have been previously published (29,30).…”
Section: Participantsmentioning
confidence: 99%
“…However, cardiovascular responses to LBNP seem to be unaffected by menstrual phase (5,16). Furthermore, venous compliance and capacitance do not change over the course of the menstrual cycle (36).…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…In female subjects, testing was not carried out at a specific phase of the menstrual cycle, as it has been shown that this does not affect orthostatic tolerance. 21,22 Measurements of CBF velocity, cerebral oxygenation, arterial BP and end-tidal gases During each session, CBF velocity, cerebral oxygenation, arterial BP, end-tidal carbon dioxide (P ET CO 2 ) and electrocardiography were recorded continuously. Blood flow velocity in the right middle cerebral artery was measured using a 2-MHz pulsed Doppler ultrasound system (DWL Doppler, Sterling VA, USA).…”
Section: Experimental Designmentioning
confidence: 99%